Technoculture Approach in Facing the Transnational Threat - Munaf, Dicky R.; Veraningsih, Maya (The ITB Journal Publisher, 2016)
Around the world, several cases strongly affect human beings. The world is not peaceful, conflict seems persistent and intractable. Moreover, after a decade of complacency, we seem to finally grasp the fact that we are fighting for survival under the shadow of catastrophic dangers. In this situation, our strategy must be radically changed so it will involve: ends, ways of action, and means to achieve our national goals. We must also redefine our understanding of security threats and strategic doctrines must also be reconsidered. We propose to defeat transnational crime. We should strive to engender and develop a strong civil society and include technology in it. Thus, the techno culture approach points to an alternative strategy for facing the transnational threat.Keywords. threat, transnational, technoculture, public-privateÂ Di seluruh dunia, beberapa kasus kejahatan secara kuat mempengaruhi umat manusia. Dunia tidak damai, konflik tampak terus terjadi dan sulit dikendalikan. Bahkan, setelah satu dekade dengan kepuasan, kita akhirnya melihat fakta bahwa kita sedang berjuang untuk bertahan di bawah bayang-bayang bencana. Dalam situasi ini, strategi kita harus berubah secara radikal sehingga akan melibatkan: akhir, cara bertindak, dan cara untuk menggapai tujuan nasional. Kita harus mendefinisikan ulang pemahaman kita akan ancaman keamanan dan doktrin strategis harus dipertimbangkan. Kita mengusulkan untuk mengalahkan kejahatan lintas negara. Kita harus berupaya memunculkan dan mengembangkan masyarakat sipil yang kuat dan memasukkan teknologi di dalamnya. Oleh sebab itu, pendekatan teknokultur merujuk kepada strategi untuk menghadapi ancaman lintas negara tersebut.Kata kunci. ancaman, lintas negara, teknokultur, pemerintah-swasta.